Indexation Rules, Risk Aversion, and Imperfect Information - Corrado Benassi; Antonello Scorcu (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
Nominal wage adjustment is modeled as resulting from bargaining between a risk neutral …rm and a risk averse worker, in an environment where the rate of ination is a random variable. Risk aversion makes for endogenous indexation arrangements, which deliver partial indexation as they exploit imperfect ination indices; risk aversion also generates a positive correlation between indexation and ination variance. The model suggests a distinction between complete vs incomplete ination adjustment on the one hand, and perfect vs imperfect adjustment on the other hand.
Keywords: 330